Early sport specialisation: Is it really the superior approach to develop young athletes into elite sporting champions? - Hallett, J. J. A. (Journal of Australian Strength and Conditioning, 2021)
The purpose of this review is to examine the available evidence on early sport specialisation and the associated physical, cognitive and psychosocial effects on youth athletes. This review also aims to identify the background and influencing factors that push the idea to specialise early and recommend helpful guidelines to consider before selecting early sport specialisation. Ultimately, answering the question, 'is early sport specialisation the best method in developing successful elite athletes later in life, or is there a superior approach?'. A review of the literature and research between 1988 and 2020 related to early sport specialisation was performed by accessing the Edith Cowan Database and Google Scholar. Combinations of keywords and phrases were included in the selection criteria: early sport specialisation, early sports diversification, long-term athlete development and youth sport. A total of 32 articles were found, with another 13 additional pieces identified as references listed. The application of early sport specialisation before the age of 12 has been associated with physical, cognitive and social risks that may be detrimental to long-term sport participation and elite sporting success. Young athletes who sample multiple sports early only to specialise later have been linked to reduced physical, psychological and social risks, greater skill transferability between sports, stronger intrinsic motivation towards the chosen sport and longer-lasting sporting careers. Exposure to multiple sports provides various situations and environments for new physical skill development and social development from player and coach interactions. In conclusion, it may be necessary for parents and coaches to heavily consider any potential risks of early specialisation before choosing to adopt this approach in the hopes to develop an elite sporting champion.